Bidirectional positive associations between problematic pornography use and body dissatisfaction in women and men: Findings among Hungarian young adults in a one-year longitudinal study - Demirgül, SA; Demetrovics, Z; Czakó, A; Paksi, B; Kökönyei, G; Bothe, B (My University)
Previous studies have established a positive link between pornography use and body dissatisfaction (BD). Nevertheless, previous empirical studies have yielded inconsistent associations between pornography use and BD when taking into account different forms of pornography use (e.g., pornography use frequency or problematic pornography use) or potential gender differences. Given that problematic pornography use (PPU, out-of-control use with negative consequences) differs from general pornography use, the associations between PPU and BD warrant further examination using a longitudinal design and large sample, which the current literature lacks. Given these limitations, this study examined the associations between PPU and BD cross-sectionally and longitudinally in a sample of Hungarian young adults. Among a sample of 2801 adults (Mage = 28 years, SD = 4.75, 47.69 % men and 52.30 % women), we performed an autoregressive cross-lagged analysis with a multi-group approach. According to the findings, greater levels of PPU were cross-sectionally associated with higher BD among men and women. Longitudinally, we observed bidirectional positive associations between PPU and BD over time among men and women as well. Based on the present findings, clinicians should implement systematic screening procedures for BD symptoms among individuals exhibiting signs of PPU. Similarly, individuals presenting with BD should be assessed for PPU. This dual-screening approach will enable timely intervention and the development of comprehensive treatment plans.
Keywords: Problematic pornography use; Body dissatisfaction; Longitudinal design; Adults